Using WeChat as an educational tool in MOOC-based flipped classroom: What can we learn from students’ learning experience? - Huang, Lanzi; Wang, Kai; Li, Shihua; Guo, Jianwen (Frontiers in Psychology, 2023)
Despite its importance, interaction remains limited in MOOC-based flipped classroom (MBFC) Grounded in social learning theory, we proposed an MBFC approach supported by social media to facilitate students’ interaction with peers and learning performance. A quasi-experiment was conducted to compare the MBFC approach (N = 58) based on WeChat with the conventional MBFC approach (N = 52). The results revealed that the use of WeChat in an MBFC approach led to better performance in terms of watching video lectures and completing online exercises before the class; however, it did not significantly enhance student learning performance compared to the conventional MBFC approach. In addition, the study found that students were moderately satisfied with the MBFC approach supported by WeChat. According to a WeChat interaction quantity and quality analysis, students’ non-substantive postings are much higher than students’ substantive postings in WeChat interaction groups, but students’ contributions to the postings have no significant effect on the final marks. Findings from this study could be of valuable reference for practitioners and researchers who plan to leverage social media tools such as WeChat to support student MOOC learning.